Protective Role of Sulodexide on Renal Injury Induced by Limb Ischemia-Reperfusion - Yuan, Tao (Evid Based Complement Alternat Med, 2021)
BACKGROUND: Though widely known as a potent antithrombin agent with protective effects on the kidney and other remote organs, it is currently ambiguous when it comes to sulodexide's function on ischemia-reperfusion (I/R) injury. With this research, we pursued to further explore how sulodexide exerts its influence on limb I/R injury, in which deleterious effects on the kidney were what we primarily focused on. METHODS: We randomized twenty-four C57BL/6 male rats into three groups, namely, sham operation group (control group), I/R group, and sulodexide pretreatment group. Hematoxylin and eosin staining was applied for discovery of renal histological changes. Serum creatinine (Cr) and serum urea nitrogen (BUN) were measured. Apoptotic parameters were detected by the TdT-mediated dUTP Nick-End Labeling method. To what extent and levels that antiapoptotic and proapoptotic proteins were expressed could be sensitively revealed by immunohistochemistry assay. Lipid peroxidation product propylene glycol and inflammatory factors were examined by enzyme-linked immunosorbent assay. Additionally, an extracorporeal hypoxia-reoxygenation (H/R) model of human renal proximal tubule epithelial HK2 cells was established. Our targets lay in cell proliferation and apoptosis, and we used western blotting to reflect apoptosis-related gene expression. RESULTS: The levels of serum BUN, Cr, and inflammatory factors in sulodexide-intervened rats manifested significant reduction when compared with the I/R group. Also, sulodexide could protect the kidney from histological changes and could effectively inhibit intraparenchymal apoptosis. Furthermore, adding 2 μl/mL or 5 μl/mL of sulodexide to H/R model cells in vitro gave rise to significant restoration of the degenerative proliferation capacity of the HK2 cells following H/R injury and late cellular apoptosis experienced dramatic reduction versus the H/R group. When treated with 5 μl/mL of sulodexide at a dose of 10 mg/kg, the levels of the antiapoptotic proteins were increased, while the proapoptotic proteins showed opposite trends. Notable escalation on antiapoptotic protein expression level, in contrast with the opposite trends exhibited in proapoptotic proteins, was observed with 5 μl/mL sulodexide pretreatment with the dosage being 10 mg/kg. CONCLUSION: Sulodexide can protect against kidney damage caused by I/R injury of the lower limbs by enhancing cell proliferation, inhibiting apoptosis, reducing inflammatory reactions, and scavenging oxygen free radicals.